Analysis of Wireless Local Area Network (WLAN) at Sirajul Falah Vocational School, Parung, Bogor - Selawati, Arina; Astuti, Rachmawati Darma; Zumarniansyah, Ainun; Juningsih, Eka Herdit; Zuama, Robi Aziz (Universitas Pendidikan Muhammadiyah (UNIMUDA) Sorong, 2024)
The world of education is currently increasingly prioritizing technology in facilitating and developing the teaching and learning process, such as the Wireless Local Area Network (WLAN) at Sirajul Falah Parung Bogor Vocational School which utilizes technology and computer networks to facilitate the responsibilities and duties of staff, teachers and school principals . Wireless Local Area Network (WLAN) is a computer network that is connected using conducting media (non-cable) using frequencies and standards according to wireless network standards. This research uses observation research methods, interviews and literature studies with the aim of finding out the working system of the Wireless Local Area Network (WLAN) at Sirajul Falah Vocational School Parung Bogor and overcoming the deficiencies found such as poor security systems and user management which often results in a large number of users who illegally used the Wireless Local Area Network (WLAN) at Sirajul Falah Vocational School Parung Bogor which also caused other connection problems. One solution that can be taken to overcome the problems found is to carry out management on the Wireless network, namely activating a different username and password feature for each user who is allowed to access the Wireless Local Area Network (WLAN) network at SMK Sirajul Falah Parung Bogor.